PERSENTASE RATA-RATA TINGKAT KEMISKINAN DI KABUPATEN ALOR, LEMBATA, ROTE NDAO, DAN SABU RAJUA TAHUN 2020 SAMPAI TAHUN 2024 - Orlando De Rois Lapuilana; Melki l. Puling Tang; Jon A. Lalang Yame; Imanuel Puling (CV. ADIBA AISHA AMIRA, 2025)
This study was conducted to see the effect of economic growth on poverty in Indonesia, the data used is secondary data from the World Bank, Bank Indonesia and the Central Statistics Agency in 1990-2022. This study uses secondary data from the Central Statistics Agency. The variables used are the poverty depth index, the poverty severity index and the percentage of poor people. Data was taken from the Alor Regency Statistics Agency (March 2020-20240). The analysis was carried out using descriptive analysis with map charts and cluster analysis. Cluster analysis is a multivariate method that aims to group objects based on similar characteristics (Hair at all, 2006). Cluster analysis classifies objects so that each object that is closest in similarity to another object is in the same cluster (Chen, 2008). The two methods in this analysis are the hierarchical method and the non-hierarchical method. This study uses a combination of both methods. First use the hierarchical method then continue with the non-hierarchical method. This model can explain short-term, medium-term and long-term behavior.